That Used to Be Us : We Went Wrong With America and How it Can Come Back - Friedman, Thomas L. and Mandelbaum, Michael (London Little, Brown, 2011)
America has a huge problem. It faces four major challenges, on which its future depends, and it is failing to meet them. Here, the author analyses those challenges and spells out what needs to be done now to rediscover America's power and prowess.
Include Index
Keywords: United States -- Education and state -- Creative ability -- Information technology--Social aspects -- Politics and government -- Budget deficits